2018
DOI: 10.12688/f1000research.14284.2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of implementation of “mental health nursing students’ clinical competency model” on academic performance of nursing students

Abstract: Background: Clinical nursing competence in mental health is one of the most important topics in theoretical and practical nursing training with many factors affecting it. The purpose of this study is to determine the impact of the implementation of the “mental health nursing students’ clinical competence model” on nursing students’ academic performance. Methods: This study is a semi experimental following one group of student nurses. “mental health nursing students’ clinical competence model” for undergraduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This study showed that the SAQ score was not significantly different between psychiatric nurses and domestic norms. Hence, although psychiatric nurses are reluctant to work in psychiatric settings due to stressors associated with working in psychiatric settings, emotional burnout, and negative public attitudes toward psychiatric settings (Rahmani et al, 2021), studies have reported that most nurses choose to work in psychiatric hospitals only when there are no other employment opportunities (Atashzadeh-Shoorideh et al, 2018). For those engaged in psychiatric nursing, it does not affect the overall self-acceptance attitude.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the SAQ score was not significantly different between psychiatric nurses and domestic norms. Hence, although psychiatric nurses are reluctant to work in psychiatric settings due to stressors associated with working in psychiatric settings, emotional burnout, and negative public attitudes toward psychiatric settings (Rahmani et al, 2021), studies have reported that most nurses choose to work in psychiatric hospitals only when there are no other employment opportunities (Atashzadeh-Shoorideh et al, 2018). For those engaged in psychiatric nursing, it does not affect the overall self-acceptance attitude.…”
Section: Discussionmentioning
confidence: 99%
“…Due to technology advancement and changing the health needs of the communities,[ 11 14 25 ] advancing nurses’ roles and the continuous shortage of nursing staff have caused challenges such as the use of unskilled nurses to provide adequate care;[ 11 14 26 ] hence, there is a need to assess the professional competency of nurses in order to educate prevention of possible harms and diseases, to provide effective, safe and respectful care for individuals and communities. [ 7 14 27 28 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Nurses' lack of interest (LOI) in working in psychiatric settings is a major factor contributing to the shortage of nursing staff in these settings. A study reported that most nurses choose to work in psychiatric settings only when there is no other employment opportunity [7]. Factors affecting their interest in working in psychiatric settings are their negative attitudes towards work in these settings [8], stress, and emotional burnout [9].…”
Section: Introductionmentioning
confidence: 99%